Language challenges and coping strategies in English Medium Instruction (EMI) science classrooms: a critical review of literature - Pun, JKH; Fu, X; Cheung, KKC (Taylor and Francis, 2023)
In classrooms worldwide, the use of English to teach science subjects is becoming increasingly common. There is an increasing number of English-as-a-second/foreign-language learners studying science in English. This review examines 66 empirical studies on this topic published from 2000 to 2021. We critically review and synthesise evidence of the language challenges faced by teachers and students in secondary and tertiary English medium instruction (EMI) science courses, as well as proposed coping strategies. By adopting a multidisciplinary approach, we examine our findings from three fields of research: science education, language policy and applied linguistics. Our study extends EMI research by combining language learning and canonical content learning. Our synthesis of previous findings enhances understanding of content teaching in a second/foreign language in language immersion classrooms (e.g. content and language integrated learning, content-based instruction) and provides evidence-based pedagogical suggestions for enhancing EMI science teachers’ instructional practices worldwide.